KAPABILITAS PEMERINTAH DAERAH DALAM UPAYA PENGENTASAN KEMISKINAN MELALUI PROGRAM RUMAH LAYAK HUNI (RLH) DI KOTA PEKANBARU TAHUN 2022 - Fazillah, Nur; Rafi, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to determine the extent of local government capabilities in supporting the success of the Livable Housing Program. The method used is a qualitative descriptive method, with data collection including interviews, observation, and documentation. The theory used is the core capability theory according to Leonard-Barton in Suherlan, covering four dimensions, namely knowledge and skills, technical systems, managerial systems, and values and norms. The results of the study show that the capabilities of the Pekanbaru City Government in poverty alleviation through the 2022 Livable House Program are not yet optimal because there are still weaknesses in the aspects of knowledge, technical systems, managerial systems, and values and norms. Each dimension was analyzed to understand the strengths and weaknesses of the local government in implementing the program, as well as the challenges faced in the social and administrative context in Pekanbaru City in 2022. Keywords: Capability, Poverty, Livable Housing Program